Viscoelastic properties of rabbit osteoarthritic menisci: A correlation with matrix alterations. (January 2017) - Levillain, A.; Magoariec, H.; Boulocher, C.; Decambron, A.; Viateau, V.; Hoc, T.
Abstract: The aim of this study was to evaluate the effect of early osteoarthritis (OA) on the viscoelastic properties of rabbit menisci and to correlate the mechanical alterations with the microstructural changes. Anterior Cruciate Ligament Transection (ACLT) was performed in six male New-Zealand White rabbits on the right knee joint. Six healthy rabbits served as controls. Menisci were removed six weeks after ACLT and were graded macroscopically. Indentation-relaxation tests were performed in the anterior and posterior regions of the medial menisci. The collagen fibre organization and glycosaminoglycan (GAG) content were assessed by biphotonic confocal microscopy and histology, respectively. OA menisci displayed severe macroscopic lesions compared with healthy menisci ( p =0.009). Moreover, the instantaneous and equilibrium moduli, which were 2.9±1.0 MPa and 0.60±0.18 MPa in the anterior region of healthy menisci, respectively, decreased significantly ( p =0.03 and p =0.004, respectively) in OA menisci by 55% and 57%, respectively, indicating a global decrease in meniscal stiffness in this region. The equilibrium modulus alone decreased significantly ( p =0.04) in the posterior region, going from 0.60±0.18 MPa to 0.26±012 MPa. This induced a loss of tissue elasticity. These mechanical changes were associated in the posterior region with a structural disruption of the superficial layers, from which the tie fibres emanate, and with a decrease in the GAG content in the anterior region. Consequently, the circumferential collagen fibres of the deep zone were dissociated and the collagen bundles were less compact. Our results demonstrate the strong meniscal modifications induced by ACLT at an early stage of OA and highlight the relationship between structural and chemical matrix alterations and mechanical properties. Graphical abstract: Highlights: Healthy and osteoarthritic (OA) rabbit menisci were characterized in two regions. OA menisci displayed severe macroscopic tears 6 weeks after OA induction. The viscoelastic properties of OA menisci significantly decreased in both regions. The collagen fibres were less compact and more undulated in OA menisci. The GAGs content significantly decreased in the anterior region of OA menisci.